A longitudinal cross-sectional study on awareness of contraception - Thakur, Srishti; Mohi, Manjit Kaur; Pathak, Nayana; Sandhu, Kandy (Indian journal of obstetrics and gynecology research, 2023)
Contraception is a method or a way to stop or prevent pregnancy. Since from ancient times birth control has its prevalence but the safest and most efficient methods of contraception was only introduced in 20th century. An ideal contraceptive is considered when it is user-friendly, effective and reversible with less or zero side effects and lesser adverse complications and more importantly one which is easily available. There are wide range of contraception or birth control methods currently available which includes traditional methods, barriers, oral contraceptives pills (OCP), implants, Intra Uterine Devices (IUDs) and Surgical methods along with injectable. The United States Center for Disease Control and Prevention jointly with World Health Organization has provided with guidelines on the safety of contraception for women with specific medical condition. According to another report documented by World Health organization, which stated that most effective and safest methods of contraception is sterilization by means of vasectomy in males and in cases of females by means of tubal linguation, intra uterine devices and implantable birth control. This data of safest birth control method also includes vaginal rings, oral pills, patches and injections. World Health Organization Department of Reproductive Health and Research has also stated that less effective methods includes physical barriers & spermicide and the least effective methods of contraception is traditional or natural method. A longitudinal cross-sectional study was conducted in the Department of Obstetrics and Gynecology at Gyan Sagar Medical College and Hospital in Punjab, India. Ethical approval was taken from the committee before commencing of this study. To determine the prevalence of awareness of Contraception and to determine the most commonly used contraceptive method among subjects. We hereby conclude our longitudinal cross-sectional study by indicating the fact that prevalence of awareness of contraception is higher in urban and educated classes of our society. We thereby wanted to spread one message through our study so that special initiative on birth control method should be mandated by Government in various medical colleges and hospitals in India to create awareness in rural sections and interior villages, social awareness of safe sexual practice could be spread each and every section of our country because contraception does not only prevent pregnancy it also protects the mankind and save one’s life from HIV and other sexually transmitted infections. As is always quoted correctly that “Prevention is better than cure”.